Epistolary Genre as Important Source of Historical-Pedagogical Researches - Tetyana Zavgorodnia (Pedagogical Discourse, 2013)
The value of epistolary genre as an important source of studying the history of public, state, political idea, Ukrainian culture and history of development of the pedagogical opinion in different historical periods, in particular, the problems of study and education is revealed in the article. The ideas of the paternal pedagogics are grounded on the example of studying the letters of famous personalities, contribution of their authors to the development of the pedagogics, theory and practice of education and self-education. The attempt to prove that epistolary genre is an important source of historical-pedagogical researchesis done.